An Effective and Playful Way of Practicing Online Motor Proficiency in Preschool Children - Eleanna Adamopoulou; Konstantina Karatrantou; Ioannis Kaloudis; Charalampos Krommidas; Vassilis Gerodimos (MDPI AG, 2024)
The children's fairytale is a playful educational tool that can be modified in such a way to enhance motor proficiency. This study investigated the effect of an online exercise program with modified fairytales on children's motor proficiency during the kindergarten curriculum. Forty preschool children (20 girls and 20 boys; 5.13 ± 0.24 years old) were divided into two equal groups: an intervention (IG) group and a control group (CG). The IG followed a 3-month (3 times/week) online exercise intervention program (supervised by the class's kindergarten teacher) with modified children's fairytales, during the COVID-19 pandemic, with an aim to improve their motor proficiency. The CG did not attend any exercise intervention program. The Democritos Movement Screening Tool for Preschool Children (DEMOST-PRE), consisting of ten tests, was used to assess the children's motor proficiency. Τhe IG, after the end of the intervention program, significantly improved in the DEMOST-PRE total score (p < 0.001; mean change: 40.7%), while the CG did not significantly improve in the total score (p > 0.05). Furthermore, in the IG, a significant negative correlation between the pre-training DEMOST-PRE total score and the percentage change following the intervention (r = −0.64; p = 0.002) was observed. A modified exercise program using children's fairytales may be incorporated into the kindergarten curriculum as an effective educational tool for the improvement of motor proficiency.